Framing analysis of Bromo fire news in Metro TV editorial review: Pan and Kosicki’s perspective - Khusnul Khotimah; Hengky Fairuz Busthomy (Universitas Aki, 2024)
This research aims to explain the framing contained in the Editorial Review Media Indonesia Metro TV program